Places and tourists: ties that reinforce behavioural intentions. Issue 1 (2nd January 2017) - Silva, Ricardo; Correia, Antónia
Abstract: This study examines the tourist/destination relationship, in particular the emotional dimension of this relationship via the place attachment construct, in the Alentejo region. A model in which the affective component (satisfaction, trust, place attachment and commitment) plays a role between the cognitive and conative component (behavioural intentions) was proposed. The model was empirically tested with a convenience sample of 814 tourists. A structural equation model (SEM) was applied using AMOS 21. The results suggest that the emotional relationship between tourists and destinations plays an important role in behavioural intentions with place attachment being critical to enhance this relation. At the managerial level, these results suggest that strengthening emotions and attachment is a must to retain tourists and is one of the main issues in tourism destination marketing.